DISPERSI GEOGRAFIS PERUSAHAAN TERHADAP PENGHINDARAN PAJAK DI INDONESIA - Putri, Dhea Safira; Kristanto, Ari Budi (Balance : Jurnal Akuntansi dan Bisnis, 2021)
The purpose of this study is to examine the influence of companies’ geographical dispersion on tax avoidance. The population in this research comprises all non-financial companies listed on the Indonesian Stock Exchange (IDX) in 2018. Moreover, 212 companies obtained using a purposive sampling method. The independent variable was geographical dispersion which measured using the standard deviation of the distance between the head office and branches. The higher standard deviation represents the more geographically dispersed company. Tax avoidance as the dependent variable was measured using the Effective Tax Rate (ETR). The lower ETR represents higher tax avoidance. Moreover, this research was included profitability as the controlling variable. The hypothesis was tested using multiple linear regression. It was indicated that geographical dispersion had a negative impact on tax avoidance. The more dispersed company, exhibit lower tax avoidance practices.